2008
DOI: 10.1103/physreve.78.061803
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of the computational methods used in the forced polymer translocation

Abstract: In forced polymer translocation, the average translocation time tau scales with respect to pore force f and polymer length N as tau approximately f;{-1}N;{beta} . We demonstrate that an artifact in the Metropolis Monte Carlo method resulting in breakage of the force scaling with large f may be responsible for some of the controversies between different computationally obtained results and also between computational and experimental results. Using Langevin dynamics simulations we show that the scaling exponent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 29 publications
13
59
2
Order By: Relevance
“…As a consequence, with growing chain length N and force f , the translocation exponent α also increases from α = 2ν ≈ 1.19 to α = 1 + ν ≈ 1.59. These predictions are supported by our simulation findings [13] as well as by results of Lehtola et al [14][15][16] but differ from the results of Luo et al [17]. The tensile force propagation phenomenon treated within the iso-flux trumpet model also leads to α = 1 + ν [18].…”
Section: Introductionsupporting
confidence: 81%
“…As a consequence, with growing chain length N and force f , the translocation exponent α also increases from α = 2ν ≈ 1.19 to α = 1 + ν ≈ 1.59. These predictions are supported by our simulation findings [13] as well as by results of Lehtola et al [14][15][16] but differ from the results of Luo et al [17]. The tensile force propagation phenomenon treated within the iso-flux trumpet model also leads to α = 1 + ν [18].…”
Section: Introductionsupporting
confidence: 81%
“…We have previously shown that the forced polymer translocation takes place out of equilibrium and is mainly determined by the balance between the driving pore force and the drag force exerted on the polymer on the cis side [7,8]. The drag force magnitude was shown to change with the tension propagation, which shows as an increase in the number of moving polymer beads N m on the cis side.…”
Section: Introductionmentioning
confidence: 99%
“…While the characteristics of the driven translocation seem to be largely determined by the spreading of tension on the cis side part of the polymer [22][23][24][25][26]28], a detailed conclusive explanation of how the scaling τ ∼ N α changes with applied force is still missing. In capsid ejection, where the polymer is initially in a packed conformation, tension spreading inside the capsid can hardly explain the obtained scaling, at least for higher monomer densities.…”
Section: B the Asymmetrical Porementioning
confidence: 99%
“…We have previously investigated the waiting time profiles when analyzing the effect of tension spreading in the polymer segment on the cis side during translocation [23]. The waiting time profile gives the time each bead has to wait before it exits the pore.…”
Section: Waiting Time Profilesmentioning
confidence: 99%
See 1 more Smart Citation